PELAKSANAAN PROGRAM PERPUSTAKAAN DAERAH DALAM MENUNJANG MINAT BACA ANAK USIA DINI PANDEGLANG – BANTEN - Dilla Nurkholifah; Ratih Kusumawardani; Kristiana Maryani (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2021)
Reading interest in children must be applied from an early age, the implementation of the regional library program is effective in helping children to foster a desire for children to come to the library, the desire for children to open books, and the desire for children to read books. This study aims to determine what kind of implementation of a mobile library program in supporting early childhood reading interest in the regional library of Pandeglang Regency, Banten, with a total of 3 programs. Data collection procedures were carried out by means of observation, interviews, and documentation. Data analysis using data reduction, data presentation, and drawing conclusions. From the research results, it was found that the implementation of the regional library program in supporting children's reading interest has been carried out well, because the program that has been running has been right on target, namely PAUD Kindergarten children in Pandeglang district and the program is appropriate, because in this program children are already doing activities that encourage children's desire to read.